Pendidikan Indonesia Masih Buruk? - Putri Amalya Rizkianti; Masduki Asbari; Nandita Putri Priambudi; Selvy Alhani Juni Asri (Journal of Information Systems and Management (JISMA), 2024)
The purpose of this article is to analyze a video from the Satu Persen YouTube channel entitled Why is Indonesian Education Bad? (Indonesian Education in the World). The method used in this article is the qualitative method because this method often results in an analysis and conclusion. This article discusses the problems of the current education system, and discusses Indonesia's low PISA score compared to other countries. And also discuss solutions on how to improve Indonesian education. Education is also very important for humans so that they are not left behind by developments over time and increase their knowledge. And there is also a need to develop skills because in the current era industry is developing very quickly, therefore good skills are needed so that there is no unemployment. Keywords: Indonesia, education, problem, expertise